THE INFLUENCE OF POLYSACCHARIDE COMPOSITION TREATMENT ON CHERRY FRUITS ANTIOXIDANT ENZYMES UNDER STORAGE - Vasylyshyna, O. V. (Scientific Progress & Innovations, 2020)
The effect of treatment with a solution of chitosan with salicylic acid on changing respiration rate and activity of antioxidant enzymes of cherry fruits during storage has been shown in the article. The researches were carried out during the years 2016–2019 with the fruit of Alfa and Pamiat Artemenka cherry varieties grown at L.P. Symyrenka Pomology Research Station of the Institute of Horticulture of the NAAS. Trees were planted in 2005 according to the 5 x 3 m pattern and row spacing was weed-free fallow land. For con- ducting research, 15 trees of each variety were sprayed with 100 mg/l of salicylic acid a day before harvest- ing; 1 % solution of chitosan with salicylic acid (100 mg/l) and then cherries were dried for 24 hours. They were picked from trees in four different places of the crown in the consumer stage of ripeness of each variety and type of treatment, placed in boxes №5 weighing 5kg for storage at a temperature of 1±0.5°C and a rela- tive humidity of 95±1 %. Untreated cherries were taken for control. The experiment was repeated three times. According to the research results, the respiration rate of Pamiat Artemenka and Alpha cherry fruit varieties decreased from 12 to 11 ml of CO2/kg*h during 15 days of storage. Pre-treatment of cherry fruits with salicylic acid solution enabled to reduce respiration rate by 9–15.4 %. When treated with a solution of salicylic acid with chitosan, it decreased by 27−38 %. By the end of storage, the respiration rate had fallen to 1−3 ml of CO2/kg*h. Catalase enzyme content in the control variant decreased by 1.8−2 times. When treating cherry fruits of Pamiat Artemenka and Alpha varieties with salicylic acid solution, catalase losses were reduced by 46–50 %. The combination of salicylic acid with chitosan contributed to berries’ lower losses – by 30.8−35.7 %. During refrigerated storage, ascorbate peroxidase activity increased significantly in all variants of the experiment as compared with 11–25 % in the control. Cherry fruit pretreatment in- creased its activity by 33–37.5 % for cherry fruits treated with salicylic acid solution and by 44–50 % for fruits treated with salicylic acid and chitosan solution. Thus, cherry fruit pre-treatment resulted in reducing the respiration rate by 27–38 % and also preventing the oxidative stress of the fruits, which is evidenced by 30.8–35.7% higher catalase activity and ascorbate peroxidase activity − by 44–50 %, as compared with un- treated cherry fruits.